Integrating Living Values Education by Bridging Indigenous STEM Knowledge of Traditional Salt Farmers to School Science Learning Materials - Muhamad Imaduddin; Noor Indah Simponi; Rizqi Handayani; Eny Mustafidah; Chatree Faikhamta (Universitas Pendidikan Indonesia, 2020)
The lack of bridges between formal science taught in schools and indigenous STEM knowledge is a problem that leads to the abandonment of cultural values and local wisdom. This article aimed to (1) describe the traditional salt production process by farmers and their living values education (LVE), and (2) transform indigenous STEM knowledge into scientific knowledge that can be applied to school science learning. This research was conducted in Central Java, Indonesia using observation, interviews, and literature and document review. A qualitative, ethnographic approach revealed that the traditional salt production process includes (1) draining the land; (2) making plots; (3) draining the pond plots; (4) compaction of the land surface; (5) seawater drainage; and (6) harvesting the salt. Identifiable living values include collaboration, simplicity, happiness, responsibility, and corporation. Indigenous knowledge is found in salt farmers' understanding of the characteristics and the process of salt crystal formation and their use of traditional equipment. Indigenous STEM knowledge can be transformed into school science learning materials as an example of integrating LVE.